Can Cognitive Bias Modification of Interpretations Training Alter Mood States in Children and Adolescents? A Reanalysis of Data From Six Studies. (January 2015) - Lau, Jennifer Y. F.; Pile, Victoria
Anxiety disorders are common and impairing in childhood and adolescence. Cognitive bias modification of interpretations (CBM-I) training aims to alter information biases associated with anxiety disorders by training the person to endorse benign, rather than negative, interpretations of ambiguous situations. With an expanding evidence base, CBM-I training in childhood and adolescence may provide a key opportunity to prevent the development of anxiety disorders, particularly by capitalizing on the inherent flexibility of the adolescent brain to make durable changes. This article augments existing data with a reanalysis of a large sample of data ( N = 387). The reanalysis highlights that CBM-I is (a) effective in altering interpretation styles; (b) that changes in mood state, although weak, are evident; and (c) tentatively, that effectiveness may vary across age in males and females. We conclude by offering further suggestions on which factors associated with protocol (e.g., multiple sessions) and training package (e.g., use of imagery) may maximize training effectiveness.